2023
DOI: 10.21203/rs.3.rs-2267166/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Feasibility and acceptability of ‘Low Intensity mental health Support via a Telehealth Enabled Network’ for adults with type 1 and type 2 diabetes: the LISTEN pilot study

Abstract: Background This study examined the feasibility and acceptability of the Low Intensity mental health Support via Telehealth Enabled Network (LISTEN) intervention, for adults with diabetes, facilitated by diabetes health professionals (HPs). Methods LISTEN training. Three HPs participated in three half-day online workshops, and applied their learnings during training cases (maximum four). Competency was assessed with a validated tool and achieving ‘satisfactory’ ratings for three consecutive sessions. LISTEN … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…LISTEN uses brief PST as a framework for enhancing problem-solving skills, one of seven core diabetes self-management behaviours [26]. We have demonstrated the feasibility and acceptability of training diabetes health professionals to facilitate LISTEN, and of delivering such a program to adults with diabetes [24]. Our research has also suggested potential bene ts of the approach, which need con rmation in a fully powered trial.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…LISTEN uses brief PST as a framework for enhancing problem-solving skills, one of seven core diabetes self-management behaviours [26]. We have demonstrated the feasibility and acceptability of training diabetes health professionals to facilitate LISTEN, and of delivering such a program to adults with diabetes [24]. Our research has also suggested potential bene ts of the approach, which need con rmation in a fully powered trial.…”
mentioning
confidence: 84%
“…Brief PST is typically delivered over 4-6 sessions and is suitable for delivery by a broad range of health professionals in various settings, including telephone, with high delity [20][21][22][23][24]. Pilot data suggests brief PST reduces diabetes distress and subthreshold depressive symptoms among adults with diabetesrelated retinopathy [25].…”
mentioning
confidence: 99%